The role of corporate social responsibility perceptions and perceived employer brand on organisational attractiveness - Ramdenee, Narisha (Organisational Psychology, 2021)
Background. Human capital, often referred to as talent, has become a key source of competitive advantage. Due to the scarcity and competition for such talent scholars and practitioners are constantly trying to find new ways to attract, engage and retain highly soughtafter employees. The recent recession and economic slow-down has, however, led to diminished financial resources which has meant that talent management strategies have had to shift with greater focus being placed on non-financially centred offers to attract talent. Such non-financial offers include employer branding (EB) and corporate social responsibility (CSR). Research Purpose. The aim of the present study was to investigate the role of perceived corporate social responsibility (CSR) on employer brand and organisational attractiveness perceptions. To achieve this aim, two research objectives were set. The first objective was to establish whether statistically significant positive causal relationships exist between perceptions of CSR, employer brand and organisational attractiveness (OA). The second objective was to estimate the relative importance of CSR and employer brand amongst other typical financial and non-financial reward elements or factors, i.e. when trade-offs need to be made. Research Design and Methodological approaches. An experimental research design was utilised and primary quantitative data was collected by means of convenience, i.e. nonprobability sampling. A realised sample of n=137 was obtained. To address the objectives stated above, a two method approach was utilised. Firstly, a 22 or 2 (CSR present or not present) x 2 (employer branding present or not present) full-factorial experiment was utilised to investigate the causal relationships with organisational attractiveness (the dependant variable). Participants were randomly assigned to one of four conditions and perceived level of attractiveness measured after being exposed to one of four fictitious recruitment posters in which the CSR and employer brand were manipulated. The validity and reliability of the organisational attractiveness scale was assessed using Principle Components Analysis (PCA) and calculating Cronbach α coefficients, respectively The data were then analysed using descriptive statistics and a 22 within-subjects Analysis of Variance (ANOVA). To address the second objective, a fractional experiment was used to estimate the relative importance of CSR when randomly manipulating several typical financial and non-financial total reward factors or elements, i.e. those typically offered to prospective employees to attract them, including remuneration, benefits, work-life balance, performance and recognition, and development and career opportunities. This was done by utilising Choice-based modelling (CBM) or choice-based conjoint analysis. The Preference Lab software was used to conduct this experiment and collect the data. Part-utility worths were then calculated to assess the relative importance of each of the six attributes. Finally, the conjoint utilities were then used to identify distinct cohorts of respondents using two-step cluster analysis. Results. The results of the 22 within-subjects or full factorial Analysis of Variance (ANOVA) revealed statistically significant main effects, as well as statistically significant interaction effects. Moreover, the CBM revealed that, in relation to the other four attributes (i.e. renumeration, work-life balance, career development and advancement and, performance management and recognition) CSR and employer branding were ranked as the third and fifth most important attributes, respectively. When identifying distinct cohorts of respondents, using cluster analysis, a 2-cluster and a 3-cluster solution was found. Findings. It was determined that when CSR is present there is an increase in organisational attractiveness and, when a desirable employer brand is present there is an increase in organisational attractiveness. Additionally, renumeration and work-life balance were ranked as relatively more important than CSR and, renumeration, work-life balance, CSR and, career development and advancement were ranked as relatively more important than employer branding. Contribution of the study. The present study hopefully contributes to a better understanding of the role of CSR and employer branding in talent attraction and so adds to the available literature in this field of study, as well as provides further theoretical perspectives on the importance of CSR in the field of reward- and talent-management. Practically, the insights gleaned from the data could be used by organisations to inform talent attraction strategies, practices and policies which may assist in attracting highly sought-after human capital and subsequently positively impact on organisational performance and sustainable organisational success. By better understanding the positive causal effect of CSR on employer brand perceptions and desirable organisational outcomes such as organisational attractiveness, this knowledge can be used to make a compelling business case for CSR. Augmenting the argument that CSR “..is the right thing to do” on the one hand, with evidence that CSR makes good business sense, makes for a compelling win-win argument for organisations to make greater social investments with obvious benefits for communities and society at large.